IDENTIFIKASI DRUG RELATED PROBLEMS (DRPs) YANG POTENSIAL MEMPENGARUHI EFEKTIVITAS TERAPI PADA PASIEN DIABETES MELLITUS TIPE II RAWAT INAP DI RSUD TUGUREJO SEMARANG PERIODE 2007-2008 - Sri Susilowati; wiwit pamuji rahayu (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2010)
ABSTRACT The management of Type II Diabetes Mellitus with prolonged drug therapy might affect the life qualities of patients and lead to Drug Related Problems (DRPs). Several types of DRPs frequently occur and they result in sub-optimum treatment, increased side effects and expensive costs. Objective of this study was to know about the uses of anti-diabetic drugs, prevalence of DRPs, the numbers of DRPs cases and the factors causing DRPs having the potentials to affect the therapeutic effectiveness for Type-II Diabetes Mellitus treated at Semarang Tugurejo Hospitals during the period of 2007-2008. The possible factors that might lead to DRPs were inaccuracy in the drug selection and sub-therapeutic. Non experimental, retrospective and non analytical observational study design was done. The population for this study consisted of 43 Type-II Diabetes Mellitus patients hospitalized in Tugurejo Hospital, Semarang. Sample collected by retrospectively from Hospital’s medical records of the 2007-2008 period in the whole population. The results showed there were 23,3% of the patient experienced DRPs which had the potentials to affect the therapeutic effectiveness for Type-II Diabetes Mellitus. Eleven cases of inaccuracies in selecting the drugs affected the effectiveness of the therapies. These cases of inaccuracies consisted of 5 cases of ineffective drugs, 4 cases of effective but expensive drugs, 2 cases of unnecessary combinations of drugs and one case of sub-therapeutic dosages. Key words : Drug Related Problems (DRPs), diabetes mellitus